Older drivers' experience with automated vehicle technology. (September 2021) - Classen, Sherrilene; Mason, Justin; Hwangbo, Seung Woo; Wersal, James; Rogers, Jason; Sisiopiku, Virginia
Abstract (236 words): Introduction: Adults 65 years of age and older make up a fifth of the US population, prefer driving as their primary mode of transportation, and may derive health and safety benefits from using automated vehicles (AVs), assuming they accept and adopt these technologies. Methods: This study used a repeated measures crossover design, with random allocation of 104 older drivers who were exposed to an automated shuttle and a driving simulator in automated mode (Level 4, Society of Automotive Engineers). Participants completed pre- and post-exposure surveys, to report their perceptions via the Automated Vehicle User Perception Survey. Researchers utilized a two-way mixed ANOVA to analyze time effect, group effect, and time by group interaction effects. Results: No group effects were evident, but older drivers' perceptions of safety, trust and perceived usefulness of AV technology increased after being exposed to the AV technology. The group by time interaction effects indicated significant perceptions pertaining to intention to use, trust, perceived usefulness, control/driving efficacy, and safety. Conclusions: This study contributes to the body of knowledge regarding the determinants of older adult AV technology acceptance practices. Yet, it is recommended that future studies build on this work to identify the role of different regulatory systems, levels of technology, geographical contexts, and policies–that may influence older drivers' perceptions of AV technology, before targeted policy and/or practice recommendations can be made. Highlights: Older drivers' perceived safety increased after exposure to the automated shuttle and simulator. Older drivers' trust increased after exposure to the automated shuttle. Older drivers' perceived usefulness increased after exposure to the simulator in automated mode. Automated vehicles may provide health and safety benefits if older drivers accept it.